Metabolic and transcriptional transitions in barley glumes reveal a role as transitory resource buffers during endosperm filling - Kohl, Stefan (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.